ANALISIS KINERJA ORGANISASI DINAS KEBERSIHAN DAN PERTAMANAN KOTA SEMARANG - Muhammad Rio Dewantoro; Nina Widowati (Journal of Public Policy and Management Review, 2016)
The purpose of this research is for analyzing the performance of Cleanliness and Landscaping Service of Semarang City and analyzing factors that causing the performance of Cleanliness and Lanscaping of Semarang City is not optimal yet. The problem that is existed in Cleanliness and Landscaaping Service of Semarang City is the lack of infrastructures and the lack of human resource that causing the performance is not optimal yet. According to Dwiyanto (2002:16), the rate of organization performance from public opinion is based on five dimensions : productivity, quality of services, responsivity, responsibility and accountability. The performance result that has done by the Cleanliness and Landscaping Service of Semarang City could be said well done enough from five dimensions above. But, to achieve good organization performance still constrained by productivity aspect, because the lack of infrastructures in Cleanliness and Landscaping of Semarang City, and in responsibility aspect the employees still confused to do their jobs because there is incompatibility of the majors that they had taken and their job so additional time is needed to train these employees first, beside that the employee with old age is also an obstacle of responsibility because they tend to be difficult to follow development. The conclusion of this research overall is organization performance can’t be said optimal yet because the productivity and responsibility aspect couldn’t be well done yet.